2020
DOI: 10.47009/ajcpn.2020.8.1.18
|View full text |Cite
|
Sign up to set email alerts
|

A study on Effect of Nutrition Supplementation in Children Living With HIV at ART Centre- A Prospective Observational Study

Abstract: Background: The nutritional status of people living with HIV/AIDS is related to morbidity and mortality and may predict the course of HIV infection and the management of these helps in recovery and maintenance of health status.Aims & objectives: The main aim of the current study toassess the nutritional status and nutritional supplementation in children with HIV at ART center.Subjects and Methods:A prospective observational study was conducted between May 2017 and May 2018 in a total of 100 children aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies were conducted in seven LMIC countries in South American, Asian and African continents. The majority ( n = 7, 41.2%) took place in upper-middle income countries [ 19 , 21 , 22 , 27 , 28 , 30 , 34 ], followed by low-middle income countries ( n = 5, 29.4%) [ 26 , 29 , 32 , 33 ] and low- income countries (29.4%) [ 20 , 23 – 25 , 35 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were conducted in seven LMIC countries in South American, Asian and African continents. The majority ( n = 7, 41.2%) took place in upper-middle income countries [ 19 , 21 , 22 , 27 , 28 , 30 , 34 ], followed by low-middle income countries ( n = 5, 29.4%) [ 26 , 29 , 32 , 33 ] and low- income countries (29.4%) [ 20 , 23 – 25 , 35 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one interventional study was found, trialling nutritional supplementation of 360 kcal energy and 32.2gm protein in food made from Peanut Chikki and another source. The study reported that after one year of supplementation on a daily basis the study participants showed a significant improvement in their Height-for-Age, Weight-for-Age and BMI-for-Age indices [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation